âÄâisha, Mother of the Faithful: The Prototype of Muslim Women Ulama - Harpci, Fatih (Al-Jamiah Research Centre, 2015)
Having a unique intelligence and assertiveness, âÄâisha has been regarded Islamâs ideal woman scholar. She was not only as one of the earliest reporters of the authentic sayings of the Prophet Muá¸¥ammad, but also a great source for conveying his private family life. The article seeks to show that âÄâishaâs life in the 7th century Arabia is especially remarkable when examined through the lenses of contemporary times. Her main characteristic was her critical, ever-inquisitive, and curious mind. Through the questions she was able to ask, âÄâisha became a bridge between the time of the Prophet and the contemporary Muslim life. The important role she played in the scholarly efforts of Muslim men and women in learning and teaching knowledge needs to be examined and properly emphasized. Her sound scholarship in Islamic disciplines include but was not necessarily be limited to hadith, tafsÄ«r, fiqh, literature, and poetry. Today Muslim women may take âÄâisha not only as a pious example, but follow her intelligence, curiosity, and reasoning.[Dengan kecerdasan dan kepercayaan diri yang khas, Äâisha terkenal sebagai seorang ulama perempuan yang ideal. Tidak hanya dikenal sebagai perawi hadis, dia juga merupakan rujukan yang hebat mengenai masalah-masalah pribadi dan keluarga. Artikel ini menunjukkan bahwa kehidupa seorang Äâisha pada abad ke-7 di Arabia sangatlah luar biasa pada masanya, dengan karakternya yang kritis, penuh rasa ingin tahu, dan bersemangat untuk mempelajari apa saja. Melalui pertanyaan yang dapat diajukan, Äâisha mampu menjadi jembatan antara Nabi dan kehidupan umat masa itu. Peran penting yang dia mainkan dalam dunia keilmuan serta pembelajaran dan pengajaran sangat perlu diteliti dan digarisbawahi. Pandangan-pandangannya mencakup –tetapi tidak sebatas– hadis, tafsir, fikih, sastra, dan puisi. Perempuan Islam saat ini tidak hanya dapat mengikuti Äâisha sebagai teladan kesalihan, tetapi juga mesti mengikuti kecerdasan, keingintahuan, dan penalarannya.]